Fixed capacitors for use in electronic equipment. Blank detail specification: Fixed metallized polyethylene-terephthalate film dielectric d.c. capacitors. Assessment levels E and EZ Part 2-1, (31st March 2010) - British Standards Institution,
No abstract available